Biodegradable Plastic Mulch Films: Impacts on Soil Microbial Communities and Ecosystem Functions - Bandopadhyay, Sreejata; Martin-Closas, Lluis; Pelacho, Ana M.; DeBruyn, Jennifer M. (Frontiers in Microbiology, 2018)
Agricultural plastic mulch films are widely used in specialty crop production systems because of their agronomic benefits. Biodegradable plastic mulches (BDMs) offer an environmentally-sustainable alternative to conventional polyethylene (PE) mulch. Unlike PE films, which need to be removed after use, BDMs are tilled into soil where they are expected to biodegrade. However there remains considerable uncertainty about long-term impacts of BDM incorporation on soil ecosystems. BDMs potentially influence soil microbial communities in two ways: First, as a surface barrier prior to soil incorporation, indirectly affecting soil microclimate and atmosphere (similar to PE films) and second, after soil incorporation, as a direct input of physical fragments, which add carbon, microorganisms, additives and adherent chemicals. This review summarizes the current literature on impacts of plastic mulches on soil biological and biogeochemical processes, with a special emphasis on BDMs. The combined findings indicated that when used as a surface barrier, plastic mulches altered soil microbial community composition and functioning via microclimate modification, though the nature of these alterations varied between studies. In addition, BDM incorporation into soil can result in enhanced microbial activity and enrichment of fungal taxa. This suggests that despite the fact that total carbon input from BDMs is minuscule, a stimulatory effect on microbial activity may ultimately affect soil organic matter dynamics. To address the current knowledge gaps, long term studies and a better understanding of impacts of BDMs on nutrient biogeochemistry are needed. These are critical to evaluating BDMs as they relate to soil health and agroecosystem sustainability.